Characterization and Functional Analysis of Mouse Invariant Natural T (iNKT) Cells - Bezbradica, J; Stanic, A; Joyce, S (Wiley, 2006)
Invariant natural T (iNKT) cells are innate lymphocytes that recognize CD1d‐restricted lipid antigens and have immunoregulatory properties. Human and mouse CD1d‐restricted glycolipid antigen(s) and the iNKT cell functions they elicit are highly conserved, whereby, making the mouse an excellent animal model for understanding iNKT cell biology in vivo. This unit describes basic methods for the characterization and quantification (see Basic Protocol 1) and functional analysis of murine iNKT cells in vivo or in vitro (see Basic Protocols 2, 3, and 4). This unit also contains protocols that describe enrichment of iNKT cells (see Support Protocol 1), generation of CD1d‐tetramer (see Support Protocol 2), and lipid antigen loading on cell‐bound (see Support Protocol 3) or soluble (see Support Protocol 4) CD1d.